Forest Fire Hazard in the Serra do Brigadeiro State Park (MG) - Fillipe Tamiozzo Pereira Torres; Gumercindo Souza Lima (Floresta e Ambiente, 2019)
ABSTRACT The objective of this study was to analyze the effectiveness of forest fire hazard indices for the Serra do Brigadeiro State Park region (MG). Although no weather station is present in this territory, the use of data obtained in the municipality of Viçosa (38 km distance) was effective to calculate the hazard. According to the results, the use of high and very high hazard classes to predict occurrences proved to be more efficient. The Telicyn, Nesterov, FMA and FMA+ indices showed better results when daily mean data was used while FWI responded better with daily maximum temperature and relative humidity at 3:00 p.m. The P-EVAP and FWI indices were the most efficient to predict fires in the study region.